Perfil epidemiológico: adultos portadores de HIV/AIDS no hospital universitário - Pieri, Flávia Meneguetti (2010)
Epidemiological studies have shown an important increasing dissemination of HIV virus. One of the biggest obstacle vivid by those people who work in health area it is to notice that, although well-informed, patients do not leave their dangerous habits, aiming at preventing the development of the virus HIV/AIDS. The objective of this study was to describe the epidemiological profile from adult patients with HIV/AIDS, treated in University Hospital in Londrina-PR, between 2002 and 2006.An epidemiological study quantitative. The data were collected from 497 medical records from patients with HIV, for that there was a survey. The survey was made with University Hospital (HU) with 71% of cases, and with Clinics Hospital (HC), with 29% of cases. The results showed the predominance of male sex (62%), female (38%), who lived in Londrina (65%), low scholarity level (58%), low income (68%), autonomous (20%), housewives (17%), retired (7.6%), free union, with 40% and 34%. Usually, a patient stays 9.4 days in hospital, each time. It is noticed that the proportion of deaths in both groups is very close. The lethality was 37.2% (septic shock) and 21.6% (multi organs dysfunction). The probability of surviving of a male patient with HIV virus after 10 years is about 65%, being the probability of surviving of a female patient 59.2%, in a same period of time. It is concluded that the earlier is the time of diagnosis of HIV/AIDS virus, the smaller is the probability of surviving of patients, for female or male sex. It is clear the need of implementation of educative actions on prevention to opportunist diseases and better quality of life.